2012
DOI: 10.1007/s12088-011-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Unigene-Derived Microsatellite Marker Based Variation Study of Phytophthora nicotianae Isolates Infecting Citrus

Abstract: Unigene sequence in public database provides a cost-effective and valuable source, for the development of microsatellite markers also known as unigene-derived microsatellite (UGMS) markers. In our study, genetic variation among 24 Phytophthora nicotianae isolates from five major citrus growing states of India were analysed through UGMS markers. Morphological and clustering results indicated variation among these Phytophthora nicotianae were independent of its geographical confinement and showed 62.27% polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, in the present study, P. palmivora and P. nicotianae were characterized through the amplification of ITS region that can rapidly distinguish between the two main species of Phytophthora involved in causing diseases in citrus [22]. The phylogenetic analysis based on ITS region revealed that P. palmivora and P. nicotianae isolates closely clustered with respective Phytopthora species infecting different citrus species in India and other different countries [9,31]. Thus, the study clearly showed that Phytophthora isolates collected from 31 places of Kodagu district confirmed the presence of two Phytophthora species, namely P.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study, P. palmivora and P. nicotianae were characterized through the amplification of ITS region that can rapidly distinguish between the two main species of Phytophthora involved in causing diseases in citrus [22]. The phylogenetic analysis based on ITS region revealed that P. palmivora and P. nicotianae isolates closely clustered with respective Phytopthora species infecting different citrus species in India and other different countries [9,31]. Thus, the study clearly showed that Phytophthora isolates collected from 31 places of Kodagu district confirmed the presence of two Phytophthora species, namely P.…”
Section: Discussionmentioning
confidence: 99%